A clinically useful self-report measure of psychiatric patients' satisfaction with the initial evaluation. (June 2017) - Zimmerman, Mark; Gazarian, Douglas; Multach, Matthew; Attiullah, Naureen; Benoff, Talya; Boerescu, Daniela A.; Friedman, Michael A.; Mehring, Lucille B.; Moon, Sumi; Patel, Sandhya; Holst, Carolina Guzman
Abstract: Patient satisfaction is one component of the quality of care. Studies of satisfaction in samples of established patients are biased because dissatisfied patients are more likely to have dropped out of treatment. We, therefore, sought to develop a new instrument assessing patients' satisfaction with the initial psychiatric evaluation. In the present report from the Rhode Island Methods to Improve Diagnostic Assessment and Services (MIDAS) project we describe the development, reliability, and validity of the Clinically Useful Patient Satisfaction Scale (CUPSS). The CUPSS is a brief, self-administered questionnaire covering 3 areas: clinician's attitude and behavior, office environment and staff, and overall satisfaction. A sample of psychiatric outpatients (n=412) and partial hospital patients (n=500) completed the measure immediately after their initial meeting with the psychiatrist. The scale had high internal consistency, and all item-scale correlations were significant. All items were significantly correlated with each of the indicators of global satisfaction. There was sufficient variability in satisfaction ratings to detect differences amongst clinicians. The results of the present study of psychiatric outpatients and partial hospital patients indicate that the CUPSS was minimally to not at all burdensome to complete, it had good psychometric properties, and it can discriminate amongst clinicians. Highlights: Patient satisfaction is an important component of the quality of medical care. We developed a new instrument assessing patients' satisfaction with the initial psychiatric evaluation. The Clinically Useful Patient Satisfaction Scale (CUPPS) was minimally to not at all burdensome to complete. The CUPPS had good psychometric properties, and it was capable of discriminating amongst clinicians.